The Problem and Analysis of Vibrations Appearing in an N10 Group Military Vehicle Fitted with a Manually-Operated Armament Module - Maciej DORCZUK (Analiza i problem drgań występujących w pojeździe wojskowym grupy N10 z zainstalowanym ręcznie sterowanym modułem uzbrojenia, 2019)
The article presents the results of the research, calculations and analyses conducted within the scope of the vibrations appearing in the fixtures of a single N10 group track vehicle (classification as per NO-06-A103:2005). The aim of the research was to examine the vibrations appearing in a stabilised turret weapon system (armament system), as well as the device supplying power to it. The analyses were conducted in conformity with the requirements of the Polish NO-06-A103:2005 defence standard, as well as those of MIL-STD-810F.
Keywords: Drgania pojazdu wojskowego